2021
DOI: 10.21203/rs.3.rs-862966/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Waning of IgG, total and neutralizing antibodies 6 months post-vaccination with BNT162b2 in healthcare workers

Abstract: Data about the duration of humoral response following COVID-19 vaccines are mandatory to establish appropriate population vaccination strategy. This study reports on the antibody decline observed in a population of COVID-19 naïve and COVID-19 positive individuals having received the two dose regimen of the BNT162b2 vaccine. Six months after vaccination, a significant antibody decline was observed in both COVID-19 naïve and positive individuals. The estimated half-life of total and IgG antibodies differs and ra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
32
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 21 publications
8
32
0
Order By: Relevance
“…The preliminary results of this ad-interim analysis of anti-SARS-CoV-2 humoral immunity in healthcare workers who received a complete (2-dose) cycle of Pfizer-BioNTech COVID-19 vaccination reveal that a gradual decline of total anti-SARS-CoV-2 antibodies (and hence of neutralizing potential) has occ urred 6 months after vaccination, though the antibodies values have remained still considerably higher than the method-dependent cut-off and no seronegativization seems to have occurred in either baseline seronegative or seropositive subjects. These results compared rather well with other preliminary data made available by Bayart and colleagues [6] , who also showed that the decay of anti-SARS-CoV-2 RBD total antibodies after 6 months from Pfizer-BioNTech COVID-19 vaccine administration was around 55% in seronegative healthcare workers, thus nearly identical to the 57% decrease that we found in our cohort over an identical period of monitoring. Although better medium-term response would have been theoretically expected in subjects with double immunization (i.e., SARS-CoV-2 infection followed by full vaccination), we instead found that total anti-SARS-CoV-2 antibodies reduction appeared larger in baseline seropositive than seronegative recipients (i.e., 74% vs. 52%) ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…The preliminary results of this ad-interim analysis of anti-SARS-CoV-2 humoral immunity in healthcare workers who received a complete (2-dose) cycle of Pfizer-BioNTech COVID-19 vaccination reveal that a gradual decline of total anti-SARS-CoV-2 antibodies (and hence of neutralizing potential) has occ urred 6 months after vaccination, though the antibodies values have remained still considerably higher than the method-dependent cut-off and no seronegativization seems to have occurred in either baseline seronegative or seropositive subjects. These results compared rather well with other preliminary data made available by Bayart and colleagues [6] , who also showed that the decay of anti-SARS-CoV-2 RBD total antibodies after 6 months from Pfizer-BioNTech COVID-19 vaccine administration was around 55% in seronegative healthcare workers, thus nearly identical to the 57% decrease that we found in our cohort over an identical period of monitoring. Although better medium-term response would have been theoretically expected in subjects with double immunization (i.e., SARS-CoV-2 infection followed by full vaccination), we instead found that total anti-SARS-CoV-2 antibodies reduction appeared larger in baseline seropositive than seronegative recipients (i.e., 74% vs. 52%) ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, our findings on waning NAb responses to wildtype virus among BNT162b2-vaccinees are consistent to several studies published recently. 19,27,31,32 Importantly, against the global panel of VOCs, NAb response rates and titers among Corona-Vac-vaccinees were not only significantly lower but also disappeared more dramatically just three months after the vaccinations as compared with BNT162b2-vaccinees. CoronaVac-vaccinees also exhibited lower neutralization potency index and waning spike-specific IFN- (i) and spike-specific IFN-g + CD4 + (j) or CD8 + T cells (k) to IC 50 against wild type (WT) as well as spike-specific IFN-g + CD4 + and CD8 + T cells (l) .…”
Section: Discussionmentioning
confidence: 95%
“…Our findings could be considered unexpected, since the effect of immunosuppressive therapies could reduce antibody response duration over time more rapidly compared to immunocompetent patients. In a recent report conducted in healthcare professionals, six months after a full course of BNT162b2 vaccine, antibody titer decline was observed in approximately 89.6% of cases, and approximately 45% of them became seronegative 23 . However, the peak response in these patients was reached 1 month after the second vaccine dose, which was earlier than what we observed in our series.…”
Section: Discussionmentioning
confidence: 96%